Implementasi Konsep Deep Learning dalam Transformasi Pembelajaran di SMA Negeri 2 Lolofitu Moi (Indo-MathEdu Intellectuals Journal, 2026)
Learning in schools still faces challenges in creating meaningful, active, and student-centered learning experiences, thus requiring a learning approach capable of supporting the transformation of the learning process. One relevant approach is Deep Learning, which emphasizes in-depth conceptual understanding, active student involvement, and the connection of material to real-life contexts. This study aims to describe the application of the Deep Learning concept in the transformation of learning at SMA Negeri 2 Lolofitu Moi. The study used a qualitative approach with descriptive methods. Data were obtained through observation, interviews, and documentation with informants consisting of the principal, vice principal for curriculum, teachers, and students who were selected purposively. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results show that the application of the Deep Learning concept is realized through learning that encourages student activeness, the use of varied learning strategies and media, and the association of material with real situations. Teachers act as facilitators who create interactive learning, while students are more actively involved in the process of discussion, exploration, and problem-solving. These findings indicate that the application of the Deep Learning concept supports the transformation of learning that is more student-centered and oriented towards competency development.